Socio-Economic and Mental Status of the Surrendered Timber Smugglers and Suggesting Measures to halt their Recidivism - Shukla, Prabhu Nath; Mishra, Virendra Kumar (Indian Forester, 2022)
Present study deals with an assessment of socio-economic and mental status of 372 timber smugglers. These smugglers had surrendered due to valiant effort and holistic approach shown by Sironcha Forest division of Gadchiroli district of Maharashtra, India. However, prevailing socioeconomic issues posed a threat of their recidivism. Present study revealed psycho-socio-economic conditions surrounding the person aftermath the surrender. Smugglers faced many problems prior to the surrender which included mental trauma, home sickness, breakdown of the family relation and threat of life from Naxalites. However, main reason cited for the surrender of timber smugglers was the pressure imposed by the forest department. Thus, there was a need of sustained pressure through patrolling, arresting, punishing etc. Surrender of the smugglers has brought many additional benefits for them such as increase in self-esteem and social respect, decrease in mental stress and alcohol intake, building up of family bonds. Outcomes of the present study suggests that in order to sustain the situation of forest protection, people should be given proper employment opportunity. Self-employment, agricultural activity and animal husbandry were opted by the most people. Creating a small decentralized forestrybased livelihood opportunities would also be a better option if government fails to provide alternative livelihood, there is lurking chance of returning the surrendered smugglers to back to their earlier business. Main hindrance in their development was remoteness and resulting poor infrastructure.